1992
DOI: 10.1111/j.1445-5994.1992.tb02145.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease in Asians

Abstract: From available studies, there appears to be a racial preponderance of coronary artery disease (CAD) among Indians when compared to other ethnic groups. We found that this racial difference exists even in a young Asian population with premature atherosclerosis. In this small series, these racial differences could not be explained by the commonly known risk factors for coronary artery disease--smoking, hypertension, diabetes and hypercholesterolaemia, findings similar to those found in older patients elsewhere. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The natural history of disease progression is often different from that in the indigenous population. This is clearly demonstrated with respect to cardiac conditions [14] and type II diabetes [1].…”
Section: Discussionmentioning
confidence: 91%
“…The natural history of disease progression is often different from that in the indigenous population. This is clearly demonstrated with respect to cardiac conditions [14] and type II diabetes [1].…”
Section: Discussionmentioning
confidence: 91%
“…The traditional risk factors for CHD, namely hypertension, high cholesterol, smoking and obesity do not fully explain the excess of CHD seen among South Asians (McKeigue et al, 1989). In earlier studies of lipids among South Asians, cholesterol levels have been reported to be normal or low (Rajadurai et al, 1992). However, a number of risk factors related to the metabolic syndrome (insulin-resistance syndrome) have been described in South Asians; these include an excess of noninsulindependent diabetes (NIDDM) (Ramachandran et al, 2001), increased upper body obesity with increased waist-to-hip ratio (WHR) (McKeigue et al, 1991), elevated plasma insulin (hyperinsulinaemia) and increased insulin resistance (Laws et al, 1994) all of which influence CHD risk.…”
Section: Introductionmentioning
confidence: 94%
“…In India, 25-40% of patients suffering from acute myocardial infarction (AMI) were below the age of 45 (Girija, 1997). In Great Britain, AMI occurred in Indians younger than 40 years old -and the incidence was 10 times higher than the local Caucasian population (Rajadurai et al, 1992). Studies in Singapore reported that mortality due to CAD below 30 years of age occurs 10 times more in the Indian population compared to the local Chinese (Hughes et al, 1990).…”
Section: Introductionmentioning
confidence: 98%